A Socio-Cultural Change in Saudi Arabia through the Lens of Comedy: An Analysis of the Film 'Crashing Eid' - Solihat, Ade (Perkumpulan Program Studi Film dan Televisi Indonesia, 2025)
This article analyzes the Saudi Arabian film